Diseminasi Kebijakan Pendidikan melalui Program Merdeka Belajar – Kampus Merdeka Pada Perguruan Tinggi Muhammadiyah di Makassar Indonesia - Nasrulhaq Nasrulhaq; Ahmad Harakan; Syukri Syukri; Sitti Rahmawati Arfah; Nur Khaerah; Nurbiah Tahir; Nur Wahid (Jayapangus Press, 2022)
This research discusses the dissemination of education policy by looking at the responses and insights of students, lecturers, and education staff at the University of Muhammadiyah Makassar towards the Merdeka Belajar-Kampus Merdeka (MBKM). The biggest challenge in implementing educational policies in higher education is the percentage of understanding of the academic community and their readiness to implement education policy packages implemented by the government. In this study, a qualitative method was used by using a case study at the University of Muhammadiyah Makassar. The data was obtained from the results of a survey to students, lecturers, and education staff conducted by the MBKM Grant Team of the University of Muhammadiyah Makassar through a survey platform and survey questions facilitated by the Ministry of Education and Culture of the Republic of Indonesia starting on 18-22 December 2021. The results of the survey processed using the Nvivo application. There have been various responses regarding the Independent Learning-Kampus Merdeka Program and it can be concluded that the dissemination of the MBKM policy still needs to be maximized, because there are still many educators and students who do not know the nature of the policy.